Rebel Movements & Autonomy: “A Similar Path, divergent Outcomes” A Comparative Analysis between the Zapatista Movement in Mexico, The Kurdish Movement in Turkey & The Polisario Front in Morocco - Mostafa, Amira (AUC Knowledge Fountain, 2021)
This thesis explores the factors that can explain why some rebel movements attain territorial autonomy while others do not. This was studied through a cross-regional comparison of three movements, the Zapatista movement in Mexico, the Kurdish movement in Turkey and the Polisario Front in Morocco. These cases were chosen with the aim to present a causal inference of their divergent outcomes, especially that the three rebel movements primarily sought to achieve some measure of self-determination. While it was relatively attained by the Zapatista movement through territorial autonomy, the Kurdish movement has been listed as a terrorist organization and the Polisario Front is outlawed in Morocco. Therefore, this thesis’s main aim is to answer the question of why some rebel movements attain territorial autonomy while others do not? I hypothesize that there are three factors that might affect the dynamics of the rebel movements and explain this research question. These are the extent of transnationalism and popular support of the movement, external intervention, and the level of democracy within the state. I also propose that these factors exist and interact in a particular sequence and configuration that result in divergent outcomes.